PENDIDIKAN PADA MASA RASULULLAH SAW DI MAKKAH DAN DI MADINAH - Annisa Rasyidah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
Before the arrival of Islam, the life of the Arab community was known as Jahiliyyah, which is a bad civilization and a cruel act that cannot be accepted by reason. Seeing the many deviant behaviors towards Arab society before the arrival of Islam illustrates the damage to the human system of life, both in the field of creed, moral worship which subsequently affects the damage to the economic, social, political, cultural, legal, and educational systems. With the presence of the Prophet there will be changes, changes that occur not only in human behavior but in the perspective and education system brought by the Prophet. The implementation of education in the time of the Prophet was based on direct guidance and guidance from Allah SWT. The education in Makkah focuses on fostering the creed, morals and monotheism of the Arab community, while education in Medina focuses more on social and political fostering.